DRIED ROSELLE (Hibiscus sabdariffa) PETALS INFLUENCE ON SERUM CHOLESTEROL LEVEL - Fitri, Kartika Yuana (Majority, 2015)
Abstract Cholesterol is the main sterol in human body. Cholesterol is the structural component of cell membrane and plasm lipoprotein, and also the starting material in bile acid and steroid hormone synthesis. High cholesterol level may become the main cause of cardiovascular disease, such as atherosclerosis and coronary heart disease. Active substances contained in Roselle petals (Hibiscus sabdariffa) is expected to cause decreasing effect on blood cholesterol. Hypocholesterolemic effect of Hibiscus sabdariffa is caused by its components which are pectin, β-sitosterol and anthosianin, but pectin and anthosamin particularly contribute to lowers the total cholesterol. Keywords : anthosianin, cholesterol serum level, pectin, roselle petals (Hibiscus sabdariffa) Abstrak Kolesterol merupakan sterol utama dalam tubuh manusia. Kolesterol merupakan komponen struktural dari membran sel dan lipoprotein plasma, dan merupakan bahan pencetus dari sintesis asam empedu dan hormon steroid. Kadar kolesterol yang tinggi dapat merupakan penyebab utama dari gangguan kardiovaskular, seperti atherosclerosis dan penyakit jantung koroner. Kelopak Bunga Rosella (Hibiscus sabdariffa) mengandung beberapa bahan aktif yang diduga dapat menurunkan kadar kolesterol dalam darah. Secara keseluruhan diduga efek hipokolesterolemik Hibiscus sabdariffa disebabkan oleh kandungan pektin, β-sitosterol, dan anthosianin yang dimilikinya tetapi efek penurunan kolesterol total terutama dipengaruhi oleh pektin dan anthosianin. Kata kunci : anthosianin, kadar kolesterotal serum, kelopak bunga rosella (Hibiscus sabdariffa), pektin